KERUSAKAN PASCAPANEN PADA UBI KAYU HASIL PEMULIAAN SELAMA PENYIMPANAN - Heldiyanti, Rina; Sutrisno, Sutrisno; Khumaida, Nurul; Darmawati, Emmy (Departement of Agrotechnology, Agriculture Faculty, Universitas Lampung, 2020)
Postharvest deterioration is a major problem which is an obstacle for cassava handling both for conventional cassava variety and mutant variety. There are two types of postharvest deterioration on cassava, namely postharvest primary deterioration (PPD) or primer deterioration of physiological deterioration, and microbiological deterioration. Damage can be minimized by carrying out storage in optimal conditions. This study aimed to determine the level of postharvest deterioration on cassava variety R and U during 35 days of storage. The storage treatment was storage consist of 1) wooden boxes and moist sawdust storage (P1) and 2)control storage (P2). The results indicated that RP2 and UP2 produced physiological deterioration by 25% on the 7th day of storage and reached 100% on the 35th day of storage. Meanwhile, the percentage of microbiological deterioration reached more than 20% on the 14th day of storage. On the other hand, RP1 and RP2 indicated good results. Both varieties experienced only less than 25% physiological deterioration and did not experience microbiological deterioration during storage.